If It Bleeds - King, Stephen, 1947-; Patton, Will; Burstein, Danny; Weber, Steven, 1961 March 4-; King, Stephen, 1947-; King, Stephen, 1947-; King, Stephen, 1947-; King, Stephen, 1947- ([New York, NY] : Simon & Schuster Audio, 2020)
Stephen King delivers an extraordinary collection of four new and compelling novellas.
Mr. Harrigan's phone -- The life of Chuck -- Rat -- If it bleeds.
Keywords: Short stories, American; Audiobooks; Short stories; Horror fiction